1978
DOI: 10.1073/pnas.75.8.3551
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore electrochemistry: relation to intracellular iron release mechanism.

Abstract: Previous studies have shown that there is a major difference between the iron release mechanism of enterobactin, a catechol-based siderophore, and that of the hydroxamate-based siderophores such as ferrichrome. For ferric enterobactin there is an esterase that hydrolyzes the ligand during iron release. In contrast, iron is released by the hydroxamate-based siderophores and the ligands are reused in subsequent iron transport. It has been suggested that release of iron by hydroxamates occurs by reduction to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 9 publications
1
95
0
Order By: Relevance
“…18,19 The reduction potentials of the salicylate analogs of ferric enterobactin (Table 4) are well within the range of biological reductants and much higher than those typically observed for the corresponding catecholate siderophores. Noteworthy, the reduction potentials observed for the hydroxamate siderophores ferrichrome A and ferrioxamine B are in the same range (Table 4).…”
Section: Reduction Potentials Of Ferric-salicylate Complexesmentioning
confidence: 57%
See 2 more Smart Citations
“…18,19 The reduction potentials of the salicylate analogs of ferric enterobactin (Table 4) are well within the range of biological reductants and much higher than those typically observed for the corresponding catecholate siderophores. Noteworthy, the reduction potentials observed for the hydroxamate siderophores ferrichrome A and ferrioxamine B are in the same range (Table 4).…”
Section: Reduction Potentials Of Ferric-salicylate Complexesmentioning
confidence: 57%
“…Noteworthy, the reduction potentials observed for the hydroxamate siderophores ferrichrome A and ferrioxamine B are in the same range (Table 4). 18 The triserine trilactone stabilizes the ferrous over the ferric state compared with the TREN scaffold; 45 …”
Section: Reduction Potentials Of Ferric-salicylate Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this enzyme is required for the removal of iron from enterobactin analogs devoid of ester bonds (60,61). The redox potential of a ferric siderophore depends on the binding constant for iron and thus on the capacity of the molecule to be protonated at neutral pH (62). If the internal pH of E. chrysanthemi were slightly lower than that of E. coli, then iron would be easier to extract in E. chrysanthemi than in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that proteins in the outer membrane coded for by ton A and ton B genes are required for the uptake of sideromycins and Fe 3+-ferrichrome, and that the same proteins serve as receptors for phages TI, T5, and tj?80 and for colicin M (2,3,12,13,15,27,28). Acquisition of resistance to sideromycins is thought to be due to mutation of the genes coding for the ton A and ton B proteins in the outer membrane (6,9).…”
mentioning
confidence: 99%